2021
DOI: 10.1037/pag0000636
|View full text |Cite
|
Sign up to set email alerts
|

Older adults remember more positive aspects of the COVID-19 pandemic.

Abstract: The initial phase of the coronavirus disease 2019 (COVID-19) pandemic changed our lives dramatically, with stay-at-home orders and extreme physical distancing requirements. The present study suggests that how adults remember these disruptions depends, in part, on their age. In two surveys collected from American and Canadian participants during Summer 2020 (n = 551) and Fall 2020 (n = 506), older age (across ages 18-90 years) was associated with greater reflections on positive aspects of the initial phase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…After experiencing the 2013 Boston Marathon Bombing, older age was associated with an increased tendency to focus on the good that had come from the event (the heroism, the city coming together; Ford, DiBiase, & Kensinger, 2018), and 6 months later, older age also was associated with a decreased tendency to focus on the negative aspects of the event (Ford, DiBiase, Ryu, & Kensinger, 2018). A similar pattern was recently shown for reflections on the initial wave of the COVID-19 pandemic: older age was associated with an increased tendency to focus on the positive aspects (Ford et al, 2021).…”
Section: Positive Memories Retain Their Affective Strength and Act As...supporting
confidence: 52%
See 1 more Smart Citation
“…After experiencing the 2013 Boston Marathon Bombing, older age was associated with an increased tendency to focus on the good that had come from the event (the heroism, the city coming together; Ford, DiBiase, & Kensinger, 2018), and 6 months later, older age also was associated with a decreased tendency to focus on the negative aspects of the event (Ford, DiBiase, Ryu, & Kensinger, 2018). A similar pattern was recently shown for reflections on the initial wave of the COVID-19 pandemic: older age was associated with an increased tendency to focus on the positive aspects (Ford et al, 2021).…”
Section: Positive Memories Retain Their Affective Strength and Act As...supporting
confidence: 52%
“…Someone may be devastated at the time of a breakup, and only later come to realize that the relationship was not a healthy one. With time, we cannot only come to appreciate that things were not as bad as they initially seemed but also to appreciate the silver linings Ford et al, 2021; see Box 4 for discussion of how older adults may be particularly good at this).…”
Section: Positive Memories Retain Their Affective Strength and Act As...mentioning
confidence: 99%
“…Similar results were obtained by another survey performed during March and April 2020 on a sample of 776 individuals aged 18-91 years from Canada and the USA 51 . Furthermore, another study suggested that older age leads to a greater focus on positive aspects of the initial phases of the pandemic 52 .…”
Section: Human Rights Of Older Adultsmentioning
confidence: 99%
“…Neubauer, Scott, Sliwinski, & Smyth (2020) showed that retrospective overestimation of negative emotions decreases with advancing age. Although the association between age and retrospective bias in the COVID-19 pandemic has not been directly examined so far, the association between age and type of retrospective reporting has been examined, showing that older adults recalled the initial phase of the pandemic with more positive emotions than did younger adults (Ford, Garcia, Fields, Cunningham, & Kensinger, 2021).…”
Section: Research Planmentioning
confidence: 99%